A novel technique for preoperative localization of pulmonary nodules using a mixture of tissue adhesive and iohexol under computed tomography guidance: A 140 patient single‐center study - Zhang, Bingyu (Thorac Cancer, 2021)
BACKGROUND: The increase in the incidence of pulmonary nodules has made computed tomography (CT) screening a requirement for diagnosis and treatment. Small pulmonary nodule detection during video‐assisted thoracoscopic surgery (VATS) or thoracotomy is frequently challenging; however, accurate and efficient localization of nodules is critical for precise resection. Herein, we introduce and evaluate the feasibility and safety of a novel technique for preoperative pulmonary nodule localization. METHODS: From March 2018 to December 2019, 140 patients with 153 pulmonary nodules measuring <2 cm in diameter were enrolled in this study. Preoperative, CT‐guided localization was performed on each nodule with an injected mixture of tissue adhesive and iohexol. Patient and nodule characteristics, localization data, complications, surgical data, and pathological results were analyzed. RESULTS: All 153 nodules in 140 patients were successfully marked preoperatively and detected during surgery (n = 153/153). Mean nodule size was 8.7 ± 2.6 mm, and mean distance from nodule to pleura was 7.9 ± 8.2 mm. The mean procedural time was 8.7 ± 1.0 min. Nine patients (6.4%) underwent two simultaneous nodule localizations and two patients (1.4%) underwent three simultaneous nodule localizations. Pneumothorax (17/140, 12.1%), pain (6/140, 4.3%), and pungent odor (5/140, 3.6%) were the major complications. No patient required further treatment, and no allergic reactions or embolisms were observed. CONCLUSIONS: Preoperative CT‐guided nodule localization using a mixture of tissue adhesive and iohexol is an efficient technique for localizing small and impalpable pulmonary lesions, including multiple pulmonary nodules. Our study demonstrates that this novel method is safe and straightforward to implement.